Inclusive institutions and long-run misallocation - Oded Galor; Kaivan Munshiy; Nicholas Wilson (Brown University, Department of Economics, 2013)
This research advances the hypothesis that resource abundant economies characterized by a socially cohesive workforce and network externalities triggered the emergence of efficiency-enhancing inclusive institutions designed to restrict mobility and to enhance the attachment of community members to the local labor market. However, the persistence of these institutions, and the inter-generational transmission of their value, ultimately resulted in the misallocation of talents across occupations and a reduction in the long-run level of income per capita in the economy as a whole. Exploiting variation in resource intensity across the American Midwest during its initial development, the empirical analysis establishes that higher initial resource-intensity in 1860 is indeed associated with greater community participation over the subsequent 150 years, and reduced mobility and labor misallocation in the contemporary period.
Keywords: I12; J13; N3; O10; 330; Inclusive institutions; Exclusive institutions; Growth; Networks; Labor misallocation; Persistence